Pengaruh Transparansi Terhadap Pemberdayaan Masyarakat Dengan Persepsi Anggaran Pendapatan Dan Belanja Desa Sebagai Variabel Moderasi (Studi Di Kecamatan Way Tuba Kabupaten Waykanan) - Setyarini, Anik; Fahrizal, Azli; Listyaningsih, Erna (Universitas Malahayati, 2024)
The problem of ineffective use of village funds is caused by the community not being actively involved in managing village funds, and the results of previous research have linked the problem of community empowerment with the transparency factor of village fund management, so the author proposes a model for increasing community empowerment in village development by involving moderation of budget perceptions village income and expenditure on the influence of transparency on community empowerment.The survey was conducted on 99 people who work as government officials in 13 villages in Way Tuba District, Waykanan Regency, then analyzed using the partial least squares (PLS) program version 4.0. The results are in accordance with the proposed hypothesis that: (1) transparency influences the empowerment of village communities in Way Tuba District, Waykanan Regency, and (2) transparency influences the empowerment of village communities in Way Tuba District, Waykanan Regency, moderated by the Perception of the Village Income and Expenditure Budget. These results provide information to strategic decision makers at the village and sub-district levels about the importance of village community involvement and understanding of budgets in village development.